Analysis of Community Adaptation to Flood Disaster in Kaliabang Tengah Urban Village, North Bekasi, West Java Province - Cahyani, Junistya Gita; Dahlia, Siti; Harsono, R. Tricahyono Nur; Adiputra, Agung (Universitas Islam Sultan Agung Semarang, 2025)
Kaliabang Tengah Urban Village in North Bekasi is one of the areas that is routinely affected by flooding every year in Bekasi City. The frequency of flooding is 2-3 times per year, with an average flood depth of 20 cm to 1 m. This study aims to determine the adaptations made by the community of Kaliabang Tengah Urban Village, North Bekasi, West Java, in order to cope with floods. The research population comprised 2,940 households in RW 06 and RW 012, with a sample of 97 households selected through the application of the Slovin formula. Proportional random sampling was employed as the sampling technique. The results of the adaptation analysis indicated that the majority of individuals elevated their residences by an average of 50 cm to 1.5 m. During the emergency response phase, the community evacuated to higher areas. Following the flood, the entire community collaborated to clean the roads and waterways.